Women and the Sikh diaspora in California: singing the seven seas - Ranganath, Nicole (Ocean and island studies, 2024)
"This book charts the transoceanic history of South Asian women in California through their speech and songs across the twentieth century. Nicole Ranganath reimagines the history of the South Asian diaspora through an examination of gender and the dynamic interplay of water and land in the cultural history of Sikhs, a faith and cultural community that emerged in the Punjab region of north South Asia over 550 years ago. It shows how the history and music of transoceanic communities, in this case Sikhs, spilled beyond the boundaries of regions, empires and nation-states. It emphasizes the heterogeneity of the South Asia diaspora by uncovering the distinct history of women's migration experiences, as well as an alternative oceanic imaginary among Sikhs that envisions unity in the cosmos. It foregrounds the pivotal role that women played in transforming Sikh communities in California through songs and female affinities. Based on six years of fieldwork in rural northern California, it explores song as a window into the interior lives of Sikh women through their performance of diverse genres: gadar anti-colonial songs, folk music, sacred hymns, and autobiographical songs. This sonic history of South Asian women in the diaspora dislodges dominant paradigms in diaspora studies and oceanic humanities that depict men as mobile and women as stationary. Women and the Sikh Diaspora in California will interest scholars of migration, South Asia and South Asian American studies, oceanic humanities, Sikh studies, music, and women's studies. It is also essential reading for anyone who is curious about global music and migration, as well as Sikh history"--